Annual report of the Department of Agriculture (animal husbandry research), 1966/1967 - University of Malawi (1971)
Reports on observations and trial results on growth and conception rates and milk records of Malawi Zebus (MZ).Data on performance testing of MZ calves, stall feeding and grazing, beef production using MZ steers, conception, growth rates and slaughter statistics of sheep at different research sites in Malawi included.